Structural, electrical, and magneto-transport properties of Pr0.7Sr0.3MnO3: Al2O3 composites - Lim, Kean Pah; Hon, Xiao Tong; Lau, Lik Nguong; Ishak, Amirah Natasha; Wong, Yan Jing; Awang Kechik, Mohd Mustafa; Chen, Soo Kien; Shaari, Abdul Halim (Elsevier, 2022)
Incorporation of insulating secondary phase into manganite composites can enhance the low-field magnetoresistance (LFMR). This work reports the structural and electrical transport properties of (1-x) Pr0.7Sr0.3MnO3 (PSMO): x Al2O3 composites synthesised by solid-state reaction method. X-ray diffraction (XRD) patterns indicated that Mn-O-Mn bond distance and angle were disturbed due to the substitution of Al3+ at Mn-site of PSMO system. This subsequently increased the resistivity of composite samples and shifted the metal-insulator transition temperature (TMI) to lower temperatures as increasing content of Al2O3. LFMR effect was observed as the magnetoresistance values increase monotonically with the decreasing temperature.